Spatial analysis of date palm cultivation in Babylon province for the period 2006-2017 - Kadhim, Hazim (Al-Adab Journal, 2023)
This research aims to reveal the spatial variation of the cultivation of palm trees in the province of Babylon, and the cultivation of palm trees is one of the most prominent agricultural activities that occupy advanced sites at the level of the province, and the reason for this is the human and natural conditions that have a significant impact on the spread and production of palm trees in it. Since this activity formed a region specialized in palm cultivation in general, as well as the cultivation of multiple varieties of dates, this research came to find out the spatial analysis of the number of palm trees and their production in the governorate for the period from 2006-2017, in which the number of palm trees reached 6,809,583 palm trees. And then understand the nature of the distribution of these numbers and their production at the level of the administrative units that make up the province of Babil through a set of statistics, graphs and maps that show the extent of the variation in them through the use of the (Arc GIS 10.8) program, especially as they are tools that can be employed in a way that contributes to Statement of the focus of this phenomenon, and the research dealt with the spatial analysis of palm cultivation and its production, and it was found that there is an administrative unit in the province of Babylon, which is the district of Shomali, which occupied the first place in the number of palm trees and its production, and the research was limited to one type of dates to export its production in the province of Babylon.